The Lifetime and One-Year Prevalence of Concussion in Male and Female High School Students in Alberta - Amanda M. Black; Jocelyn H. McCallum; Paul H. Eliason; Brent E. Hagel; Carolyn A. Emery (Clinical Journal of Sport Medicine, 2026)
Objective: To examine the lifetime and one-year prevalence of concussion, including suspected and medically diagnosed, among high school students (ages 14-19 years) in Alberta, Canada. Design: Cross-sectional survey. Setting: High schools across Alberta, Canada. Participants: Grade 10 to 12 students from 24 schools. Independent Variables: Students completed an anonymous and validated online survey during class (October 2018-March 2019), including their sex and participation in sport and recreational activity. Main Outcome Measures: Prevalence estimates for lifetime and one-year concussion, including suspected and medically diagnosed, were estimated with 95% confidence intervals (CI) adjusted for cluster by school. Results: In total, 1972 students (97.14%) were included. At least 1 suspected lifetime concussion was reported by 292 of 923 males (31.64%; 95% CI: 24.45-39.83) and 262 of 1027 female students (25.51%; 95% CI: 20.92-30.72), and at least 1 suspected concussion in the past year by 138 of 923 males (14.95%; 95% CI: 10.92-20.92) and 118 of 1027 female students (11.49%; 95% CI: 9.07-14.46). For male students, ice hockey (16.67%; 95% CI: 12.28-22.07), lacrosse (13.79%; 95% CI: 5.27-31.52), and rugby (13.11%; 95% CI: 6.02-26.24) had the highest period prevalence of sport-related concussion in the previous year. For female students, ringette (19.05%; 95% CI: 9.92-33.46), rugby (15.52%; 95% CI: 8.04-27.84), and wrestling (12.00%; 95% CI: 3.68-32.77) had the highest prevalence. Conclusions: One in 3 male and 1 in 4 female high school students from Alberta reported at least 1 suspected concussion in their lifetime. One in 7 male and 1 in 9 female students reported at least 1 suspected concussion in the past year. Concussion prevention strategies are a key priority.